Analisis kelayakan finansial usaha perikanan tangkap di Kampung Gurimbang Kecamatan Sambaliung Kabupaten Berau - Muhammad Syafril; Elly Purnamasari; Dayang Diah Fidhiani (Fakultas Pertanian Universitas Yudharta Pasuruan, 2022)
Introduction: This study aims to measure the productivity and financial viability of the capture fisheries business in the Berau sea, which is managed by the local community of Gurimbang Village. Methods: The research was conducted in the Gurimbang Village, Sambaliung District, Berau Regency, in June-December 2020. Data analysis used financial analysis and descriptive analysis. Result: The results showed that there were fishing with fishing gear and fishing business with fishing gear 2 types of marine fisheries managed by fishermen in this village, namely, fishing nets and nets. The total income of fishing rods per trip ranges from IDR 579,580-1,804,094 with an average of IDR 863,526.34/fisherman. The income productivity of fishing rods is IDR 82,797-128,173 with an average of IDR 103,589/fisherman every day. Net and net fishermen generate income per activity trip in the range of IDR 468,612-708,929 with an average per fisherman of IDR 570,602.24, while the productivity of their income is IDR 117,153-177,232 with an average of IDR 142,651/fisherman every day. Both types of business are financially feasible to be managed as the main livelihood. Capture fisheries business managed by fishing rods produces an NPV value of IDR 102,822,888, an IRR value of 261%, Net B/C value of 9.42, Payback Value of 0.55 years and ROI of 188.44%. Fishery business with fishing gear and nets produces an NPV of IDR 81,605,621, IRR of 154%, Net B/C of 6.41 and an ROI of 128%. Conclusion: Capture fisheries business in Gurimbang village, using fishing rods, nets and nets, is financially feasible using the discounted investment criteria (NPV, IRR, Net B/C, Payback Period).